2022
DOI: 10.1186/s12906-022-03522-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety evaluation of black ginseng (Panax ginseng C.A. Mey.) extract (CJ EnerG): broad spectrum cytotoxic activity in human cancer cell lines and 28-day repeated oral toxicity study in Sprague-Dawley rats

Abstract: Background Ginseng (Panax ginseng C.A. Mey.) has been used as a valuable ingredient in traditional medicine for thousands of years mostly in Asian countries due to its therapeutic effects in various diseases. Among the processed ginseng products, black ginseng is produced by a repeated steaming and drying process of ginseng roots and has been known for its superior efficacy based on high accumulation of minor ginsenosides as recently discovered. Despite its popularity and increasing use, the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Although none of the studies was performed with the additive under assessment, some of the studies were considered relevant as P. ginseng roots were extracted with hot water or 80% ethanol resulting in concentrations of ginsenosides in the test items comparable or higher (from 2% to 10.9%) than in the additive under assessment (1%). From these studies (oral exposure: 28 days up to 2 years), no observed adverse effect level (NOAEL) values were identified in the range 2000–5000 mg/kg bw per day for the test item, ginseng extracts containing 2%–10.9% ginsenosides (Jeong et al., 2016 ; Lee et al., 2019 ; NTP, 2011 ; Park et al., 2013 , 2018 , 2022 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Although none of the studies was performed with the additive under assessment, some of the studies were considered relevant as P. ginseng roots were extracted with hot water or 80% ethanol resulting in concentrations of ginsenosides in the test items comparable or higher (from 2% to 10.9%) than in the additive under assessment (1%). From these studies (oral exposure: 28 days up to 2 years), no observed adverse effect level (NOAEL) values were identified in the range 2000–5000 mg/kg bw per day for the test item, ginseng extracts containing 2%–10.9% ginsenosides (Jeong et al., 2016 ; Lee et al., 2019 ; NTP, 2011 ; Park et al., 2013 , 2018 , 2022 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Black ginseng is made by processing ginseng under "nine steaming and nine sun-drying" to produce rare saponins with potent anticancer activity [3]. Recent studies have shown that black ginseng has anticancer [4], antioxidant [5], and immunomodulatory effects [6]. Black ginseng has a better impact against prostate cancer, according to previous research on the variations in the composition of ginseng, red ginseng, and black ginseng [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The potential biological effectiveness of black ginseng, such as anti-tumor, anti-inflammatory, antioxidant, anti-aging, and anti-diabetic activities is believed to surpass that of ginseng products derived from other processing procedures (Huang et al, 2023). However, it is worth noting that black ginseng may exhibit increased cytotoxicity in laboratory settings, which could be attributable to the unique properties of certain saponin components present in black ginseng (Park et al, 2022). No apparent abnormalities were observed in the physiological indicators, blood biochemistry, and histopathology analyses following the administration of black ginseng extract, as determined through tests conducted on rat models (Park et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is worth noting that black ginseng may exhibit increased cytotoxicity in laboratory settings, which could be attributable to the unique properties of certain saponin components present in black ginseng (Park et al, 2022). No apparent abnormalities were observed in the physiological indicators, blood biochemistry, and histopathology analyses following the administration of black ginseng extract, as determined through tests conducted on rat models (Park et al, 2022). The chemical composition of black ginseng, particularly ginsenosides, shows significant alterations during nine steaming and drying cycles, resulting in corresponding modifications to the biological activity of black ginseng (Huang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%